Life Paths of Urban Children and Youth in Comparative Perspective - Porio, Emma E (Archīum Ateneo, 1996)
The life paths of young boys and girls and their families in cities in the Philippines, India, Brazil, Kenya and Italy provide a first analysis, often in the children's own words, of the multiple overlapping crises that lead them to situations of distress. Such situations include running away to live in the streets and/or progressively falling into high risk behavior, such as dropping out of school, abusing different kinds of substances, engaging in sex for money or protection, and peddling drugs. Their life histories illustrate their resilience. But they also illustrate how the quality of their relationships to meaningful adults is being increasingly threatened and how painful and disruptive that is for these developing young people, who need the caring presence and reassuring validation of key adults, both within and outside their families, as they enter into an adult world.